Cation Substitution of Solution‐Processed Cu2ZnSnS4 Thin Film Solar Cell with over 9% Efficiency. Issue 19 (14th July 2015) - Su, Zhenghua; Tan, Joel Ming Rui; Li, Xianglin; Zeng, Xin; Batabyal, Sudip Kumar; Wong, Lydia Helena
<x xml:space="preserve">Abstract</x> To alleviate the limitations of pure sulfide Cu2ZnSnS4 (CZTS) thin film, such as band gaps adjustment, antisite defects, secondary phase and microstructure, Cadmium is introduced into CZTS thin film to replace Zn partially to form Cu2Zn1−xCdxSnS4 (CZCTS) thin film by low‐cost sol–gel method. It is demonstrated that the band gaps and crystal structure of CZCTS thin films are affected by the change in Zn/Cd ratio. In addition, the ZnS secondary phase can be decreased and the grain sizes can be improved to some degree by partial replacement of Zn with Cd in CZCTS thin film. The power conversion efficiency of CZTS solar cell device is enhanced significantly from 5.30% to 9.24% (active area efficiency 9.82%) with appropriate ratio of Zn/Cd. The variation of device parameter as a function of Zn/Cd ratio may be attributed to the change in electronic structure of the bulk CZCTS thin film (i.e., phase change from kesterite to stannite), which in turn affects the band alignment at the CZCTS/buffer interface and the charge separation at this interface.